2007
DOI: 10.2174/138161207782110507
|View full text |Cite
|
Sign up to set email alerts
|

Multiligand Endocytosis and Congenital Defects: Roles of Cubilin, Megalin and Amnionless

Abstract: Cubilin and megalin are multiligand receptors that mediate uptake of extracellular ligands. Their function has extensively been studied in the kidney where they play a key role in vitamin B12 and vitamin D homeostasis. Amnionless is a plasma membrane protein that binds to cubilin in various epithelia; the interaction cubilin-amnionless in the gut is crucial for dietary vitamin B12 uptake. Studies in patients with gene defects in these receptors, and animal models with inactivated cubilin, megalin or amnionless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 84 publications
2
31
0
Order By: Relevance
“…Mutations in any of the three genes or blocking of their function by antibodies compromises normal embryonic development in rodents, especially affecting neural tube and brain formation (29,42). The ligand binding domains of cubilin and LRP2 recognize a vast number of diverse proteins, many of which are yolk constituents, such as protein-bound vitamins, hormones, and a range of lipoproteins (28). Furthermore, we have previously shown that the YS EECs also express LR8 (the galline homologue of the mammalian VLDL receptor), which is capable of internalizing apoB-containing lipoproteins, such as VLDL (22), expanding the list of receptors involved in the uptake of yolk precursor macromolecules into the EECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in any of the three genes or blocking of their function by antibodies compromises normal embryonic development in rodents, especially affecting neural tube and brain formation (29,42). The ligand binding domains of cubilin and LRP2 recognize a vast number of diverse proteins, many of which are yolk constituents, such as protein-bound vitamins, hormones, and a range of lipoproteins (28). Furthermore, we have previously shown that the YS EECs also express LR8 (the galline homologue of the mammalian VLDL receptor), which is capable of internalizing apoB-containing lipoproteins, such as VLDL (22), expanding the list of receptors involved in the uptake of yolk precursor macromolecules into the EECs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the apoA-I-harboring EEC-derived, possibly chylomicron-like particles appear to represent a unique chicken-specific lipoprotein class. Significantly, apoA-I is a major ligand recognized by cubilin, a component of the endocytic LRP2-cubilin-amnionless receptor complex (26,28). Furthermore, apoB and apoA-V, present in the same lipoprotein fraction as apoA-I, are recognized by members of the LDL receptor family (14,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that the multi-ligand endocytic receptors cubilin and megalin exert their roles in the visceral epithelial cells of the embryonic yolk sac, intestine, kidney and thyroid gland and participate in the transportation of vitamins B12 and D3, lipid-binding proteins, poorly water soluble hormones and their binding proteins, mineral-binding proteins and a variety of heterogeneous ligands (Kaseda et al, 2011;Kozyraki et al, 1999;Kozyraki et al, 2001;Nykjaer et al, 2001;Christensen and Birn, 2002;Christensen and Verroust, 2002;Fisher and Howie, 2006;Kozyraki and Gofflot, 2007). Because cubilin mediates nutrient transport from the maternal to the fetal circulation, the loss or partial incapacitation of cubilin and megalin function could be expected to jeopardize fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced abundance of cubilin transcripts was validated by quantitative real-time (RT)-PCR in multiple embryos and yolk sacs (supplementary material Fig. S1 (Kozyraki et al, 1999;Kozyraki et al, 2001;Nykjaer et al, 2001;Assémat et al, 2005;Kozyraki and Gofflot, 2007), as well as the transport of lipids and morphogens, such as sonic hedgehog (Shh), and retinoids (supplementary material Table S3), that play crucial roles in normal embryogenesis (Kozyraki et al, 1999;Willnow et al, 1999;Fisher and Howie, 2006;Kozyraki and Gofflot, 2007).…”
Section: Effect Of Gpr107 Inactivation On Embryonic Developmentmentioning
confidence: 98%
“…Transferrin receptor mutants either exhibit no embryonic phenotypes (Trfr2 -/-) or do not exhibit defects in neural development until after 10.5 (Trfr -/-), when metabolic needs increase (Levy, 1999;Fleming, 2002). The multi-ligand endocytic receptor complex that includes cubilin (Cubn) and megalin (Lrp2) is expressed in the VE and mediates endocytosis of a number of ligands, including folic acid, Vitamin B12, cholesterol and lipids, in addition to transferrin bound to iron (for a review, see Kozyraki and Gofflot, 2007). Interestingly, megalin-null mutant embryos exhibit exencephaly and forebrain defects reminiscent of those exhibited by Fpn1 ffe/KI mutants (Spoelgen et al, 2005;Willnow et al, 1996).…”
Section: Research Articlementioning
confidence: 99%